A rare association of chronic lymphocytic leukemia with c-ANCA-positive Wegener's granulomatosis: a case report. Issue 1 (December 2016) - Bîrluţiu, Victoria; Rezi, Elena; Bîrluţiu, Rares; Zaharie, Ioan
Abstract Background Wegener's granulomatosis is a systemic vasculitis of the small- and medium-sized vessels, produced by the action of ANCA, which involves the respiratory tract, kidneys, and eyes, with a potential for lethal evolution in the first year after diagnosis. Its association with chronic lymphocytic leukemia is rarely described in the literature, and it may be difficult to diagnose and to treat this association. Case presentation We present the case of a 73-year-old Caucasian patient, a rare case in which Wegener's granulomatosis is associated in a patient with chronic lymphocytic leukemia, who is admitted in the Infectious Disease Department for fever, diplopia, headache, purulent and hemorrhagic nasal secretions, intense asthenia, and weight loss. The patient had associated eyelid edema; scleritis; chemosis; subconjunctival hemorrhage at the left eye; swelling of the left region of the eyehole, of the base of the nasal pyramid, and of the left zygomatic region; anterior nasal bleeding; pustulous non-itching lesions at the cervical region and posterior thorax; enlarged bilateral axillary lymph nodes; hepatomegaly; and moderate splenomegaly. During the surgical treatment of the pansinusitis, a biopsy from the tissue is taken; the biopsy fragments of the nasal mucosa pleads for Wegener's granulomatosis. The c-ANCA were positive. The patient's evolution was favorable under treatment with meropenem, teicoplanin, fluconazole, transfusions of platelet concentrates, and methylprednisolone. Conclusions The real dimension of the association between chronic lymphocytic leukemia and Wegener's granulomatosis is not known; it may be useful to evaluate the vasculitis by testing ANCA routinely in patients with chronic lymphocytic leukemia and by histopathological examinations of the lesions.